The Effect of Emotional Intelligence on Student Learning Achievement - Dewi Nazilatul Masruroh; Lilis Rahmawati; Ria Fakhrurriana; Chalimah Chalimah; Maskhurin Fajarina (STAI Miftahul Ula Nganjuk, 2024)
This study explores the impact of emotional intelligence on the learning achievements of students in Islamic Religious Education (PAI) for Class XI at Ulul Albab Islamic Vocational High School. Emotional intelligence is a crucial factor that influences students' ability to manage their emotions and, consequently, their academic performance. The research employs a quantitative approach, utilizing surveys and documentation to gather data from students. The findings indicate a significant relationship between emotional intelligence and learning achievement, highlighting that students with higher emotional intelligence tend to perform better academically. This suggests that emotional intelligence is a vital component in the educational process and should be nurtured alongside intellectual development to improve overall student performance in religious education.